The Effect of Sharia Financial Access & Financial Literation to Non-Bankable MSME’s Growth - Fania Mutiara Savitri; Asep Suraya Maulana; Atika Dyah Perwita; Saptana Saptana (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
A number of Islamic financial institutions able to provide non-bankable requirement by limiting loan plafond in order to reduce credit risk. That condition can hamper Micro Small Medium Enterprise (MSME)’s growth. This is proven by only 13.21% of MSME that only have been served by obtaining access to Islamic finance. Study about MSME’s Growth have general purpose to analyze interaction between Financial Literacy and Sharia Financial Access to Finance to MSME’s Growth. This study adopted quantitative research design and used Structural Equation Model (SEM) analysis method by SmartPLS 3.0 to run the data. Population in this research was all MSME’s actor in Semarang that put 100 samples contributing in this research by convenience technique. The finding of the research found Financial Literacy and Access to Sharia Finance affect performance, Financial Literacy affects Access to Sharia Finance and financial Literacy cannot be mediator for the relationship between Access to Sharia Finance to MSME’s growth.